Kemampuan Motorik Ditinjau Dari Kelincahan, Kecepatan Dan Koordinasi Mata Tangan - Maulani, Shela Aprilia; Jariono, Gatot (Jurnal Porkes, 2022)
The background of this research is to find out how well the students' motor skills are considered by the Physical Education teacher at the school in carrying out learning and choosing the right learning method, especially during practical learning outside the field. This study aims to determine the motor skills of the students of SD Negeri 1 Temuwangi, Pedan District, Klaten Regency. This research is a quantitative descriptive study, meaning that in this study only need to describe the current situation without theory. This concentration is only for the motor skills of fourth and fifth graders at SD Negeri 1 Temuwangi. The method used is a survey with the test method as an instrument for collecting data. The motor skills of grades IV and V are known that in the very high category 0 students (0%), are in the high category 1 student (4%), are in the medium category 13 students (54%), are in the low category 10 people (42% ), are in the very low category of 0 students (0%). These results indicate that the motor skills of students are in the moderate category.